Retrograde Intrarenal Surgery versus Mini-Percutaneous Nephrolithotomy for Lower Calyceal Stones of ≤ 2 cm - Shah, Rajiv; Kandel, Tika Devi; Adhikari, Deepak (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Renal stones are one of the common urological problems. The optimal management of lower calyceal renal calculi of 1-2 cm is still debatable. The objective of this research is to assess the safety, efficacy, and stone-free rate of retrograde intrarenal surgery and mini-percutaneous nephrolithotomy for the management of lower calyceal stones of 1-2 cm. Methods: A prospective comparative study was conducted among 30 patients which were divided in two group (A and B) prospectively with lower calyceal stones of 1-2 cm. Group A were treated with retrograde intra renal surgery while Group B were treated with mini percutaneous nephrolithotomy. Results: The mean age of patient in Group-A was 44.27±17.10 year and in Group-B was 45.27±16.11 year. The hospital stay in Group-A was 3.47±0.62 and in Group-B was 4.50±0.73 days. The stone size in Group-A was 13.30±2.21 mm and in Group-B was 15.60±2.55 with p-value of 0.381. The duration of operation time in Group-A was79.37±13.96 minutes and in Group-B was 62.53±7.41 minutes with p value of 0.091. Conclusions: Both retrograde intrarenal surgery and mini-percutaneous nephrolithotomy procedure are comparable. Mini percutaneous nephrolithotomy has a better stone free rate and haematuria is more common but retrograde intrarenal surgery has less hospital stay and post operative pyrexia is more common.